O design industrial e as engenharias: uma possibilidade de integração por intermédio da engenharia reversa - Silva, Danilo Émmerson Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the West, Reverse Engineering has been wrongly associated for a long time, the ilicit practices and procedures. Through this route, Eastern countries and members of the bloc Asian Tiger Triggered strategies for innovation in products and processes. More recently, with the contribution of new technologies, the ER became a member of the scanning systems and 3D inspection. Moreover, foreing literature has adopted its nomenclature to describe research with living systems and biological differently than previously believed only to produce advances technological fields. Based on these assumptions, the ER was investigated as a methodological tool that enables the integration between the areas responsible for the design and development of products and industrial artifacts - engineering and industrial design - in the productive sectors, but especially in academia. Were researched in depth, aspects of conceptualization, historicity, developments, applications and transformations in Reverse Engineering and its state-of-art and methodological framework (theoretical and scientific), and of controversial issues such as the legality and the right tangent this industrial area. Specifically, the use of analytical techniques is part of the ER, especially in the area projetual configured by industrial, design and engineering (product, production and industrial). Thus, were conducted: literature searches; applaying questionnaires and interviews in the field next to the academy and productive sectors - case factories and company; and in academia laboratories were produced tetsing, virtual simulation, prototyping and rapid manufacturing (RP/RM), analysis of products and processes, among other. The mothodological tools adopped in the compilation of data and verification of the hypotheses formulated in this research work, The results pointed to the need for convergence and integration between industrial design and engineering in both the production sector and...

Durante muito tempo a Engenharia Reversa (ER) esteve associada, de modo equivocado, no ocidente, a práticas e procedimentos lícitos. Através deste percurso, países orientais e integrantes do bloco econômico Tigre Asiático desencaderarm estratégias de inovação em produtos e processos. Mais recentemente, com o aporte das novas tecnologias, a ER fez-se integrante dos sistemas de digitalização e inspeção 3D. Ademais, a literatura estrangeira tem adotado a sua nomenclatura para designar pesquisas com sistemas vivos e biológicos, diferentemente, do que se acreditava produzir avanços somente aos campos tecnológicos. Com base neses pressupostos a ER foi investigada como um instrumento metodológico que possibilite a integração entre as áreas responsáveis pelo projeto e desenvolvimento de produtos e de artefatos industriais - enegenharias e o design industrial - engenharias e o design industrial - nos setores produtivos, mas principalmente no meio acadêmico. Foram pesquisados, em profundidade, aspectos da conceituação, historicidade, desdobramentos, aplicações e transformações sofridas na ER bem como o seu estado da arte e arcabouço metodológico (teórico-científico), além das questões controversas como a da legalidade e do direito industrial que tangenciam esta área. Desta forma, foram realizadas: pequisas na literatura; a aplicação de questionários e entrevistas em campo junto à academia e aos setores produtivos - cases de fábricas e empresas; e, em laboratórios acadêmicos, foram produzidos testes e ensaios, de simulação virtual, de prototipagem e manufatura rápida (PR/MR), análises de produtos e processos, dentre outras. Os instrumentos metodológicos adotados na compilação dos dados serviram para a verificação das hipóteses formuladas nesta pesquisa. Os resultados apontaram para a necessidade de uma convergência e integração entre o design e as engenharias tanto no setor produtivo quanto na academia...
Keywords: Desenho industrial; Engenharia; Desenho (Engenharia); Engenharia reversa; Educação; Industrial design